Design and Construction of Guest Friendly Robot for Front Office Service on Campus Based on IoT - Putri Purwani, Dea Nanda; Buaton, Relita; Milli Alfhi Syari (Yayasan Kita Menulis, 2024)
Amid the rapid advancements of the digital era, Internet of Things (IoT) technology has emerged as one of the most significant innovations, enabling electronic devices to connect and interact intelligently. This study aims to design and develop an IoT-based guest reception robot intended for front office services at the campus. The robot is designed as a prototype capable of welcoming guests, saying